2015
DOI: 10.1074/jbc.m114.634915
|View full text |Cite
|
Sign up to set email alerts
|

Post-translationally Abnormal Collagens of Prolyl 3-Hydroxylase-2 Null Mice Offer a Pathobiological Mechanism for the High Myopia Linked to Human LEPREL1 Mutations

Abstract: Background: Mutations in LEPREL1, the gene encoding prolyl 3-hydroxylase-2 (P3H2), cause severe nonsyndromic myopia. Results: Collagens I and IV from P3h2-null mouse eye tissues were significantly reduced in 3-hydroxylation compared with wild-type littermates. Conclusion: Loss of P3h2 causes altered collagen prolyl 3-hydroxylation from multiple tissues. Significance: Improved understanding of molecular mechanisms of myopia could aid in early diagnosis and treatment of irreversible vision loss.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
60
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(64 citation statements)
references
References 43 publications
2
60
0
2
Order By: Relevance
“…A recent study has shown that P3H2 expression in tendon is significantly higher than P3H1 or P3H3 (44). In addition, the 3-Hyp at Pro-707 of both ␣1 and ␣2 chain was significantly underhydroxylated in tendon type I collagen in P3H2 null mice (43). Thus, it is likely that P3H2 can hydroxylate this site without requiring CypB in tendon collagen.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study has shown that P3H2 expression in tendon is significantly higher than P3H1 or P3H3 (44). In addition, the 3-Hyp at Pro-707 of both ␣1 and ␣2 chain was significantly underhydroxylated in tendon type I collagen in P3H2 null mice (43). Thus, it is likely that P3H2 can hydroxylate this site without requiring CypB in tendon collagen.…”
Section: Discussionmentioning
confidence: 99%
“…Collagen Extraction-Type I collagen was solubilized from bone, skin, tendon, aorta, sclera, and cornea by heat denaturation for 5 min at 100°C in Laemmli buffer (SDS extraction), 3% acetic acid at 4°C for 24 h, or cyanogen bromide digestion in 70% formic acid at room temperature for 24 h. Type II collagen (rib cage cartilage), type IV collagen (kidney cortex), and type V collagen (bone and skin) ␣-chains were solubilized by pepsin digestion or cyanogen bromide digestion as previously described (17,41). Collagen ␣-chains were resolved by SDS-PAGE and stained with Coomassie Blue R-250.…”
Section: Methodsmentioning
confidence: 99%
“…This was surprising, particularly for P3h3 Ϫ/Ϫ , which is a close homolog of P3h1 and P3h2, including a potentially active catalytic domain. Both P3h1 and P3h2 have evolved preferred GPP substrate sequences in a range of collagen types (17,24,25).…”
Section: Generation Of P3h3mentioning
confidence: 99%
See 1 more Smart Citation
“…Mutations in this gene have been reported in patients with HM in western Asia (19,29) and China (30). Leprel1 knockout (KO) mice with abnormal collagen chemistry partially recapitulate the myopic changes (31). Proband H33 carries a homozygous mutation (p.Q708H) in the GRM6 gene.…”
Section: Significancementioning
confidence: 99%